Monitoring the Nervous System for Anesthesiologists and Other Health Care Professionals - Koht, Antoun; Sloan, Tod B.; Toleikis, J. Richard (Springer International Publishing : Imprint: Springer, 2017)
This widely praised, first-of-its-kind book has been thoroughly updated, expanded, and enriched with extensive new case material, illustrations, and link-outs to multimedia, practice guidelines, and more. Written and edited by outstanding world experts, this was the first and remains the leading single-source volume on intraoperative neurophysiological monitoring (IOM). It is aimed at graduate students and trainees, as well as members of the operative team, including anesthesiologists, technologists, neurophysiologists, surgeons, and nurses. Now commonplace in procedures that place the nervous system at risk, such as orthopedics, neurosurgery, otologic surgery, vascular surgery, and others, effective IOM requires an unusually high degree of coordination among members of the operative team. The purpose of the book is to help students, trainees, and team members acquire a better understanding of one another's roles and thereby to improve the quality of care and patient safety. From the reviews of the First Edition: "A welcome addition to reference works devoted to the expanding field of nervous system monitoring in the intraoperative period... will serve as a useful guide for many different health care professionals and particularly for anesthesiologists involved with this monitoring modality...An excellent reference...[and] a helpful guide both to the novice and to the developing expert in this field." -- Canadian Journal of Anesthesia "Impressive... [The book] is well written, indexed, and illustrated...The chapters are all extensively referenced. It is also very good value at the price....I would recommend this book to all residents and especially to all neuroanesthesiologists. It will make a worthwhile addition to their library." -- Journal of Neurosurgical Anesthesiology.
Keywords: Medicine.; Anesthesiology.; Neurosurgery.; Pain medicine.; elektronické knihy; electronic books